2016
DOI: 10.4028/www.scientific.net/amm.861.255
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Microorganisms on Insulated Facades in the Selected Location (Ostrava-Poruba)

Abstract: Incidence of microorganisms on thermal-insulated facades in the selected location (Ostrava-Poruba). Incidence of microorganisms on facades is more and more common. It benefits mostly from façade´s thermal insulation. This problem is not only esthetical. Incidence of microscopic fungi increased due to environmental changes. Every person is breathing spores (reproductive particles of mould) unknowingly. There is evidence that spores are closely related to respiratory illnesses. Objects that are vulnerable to mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Measurements in this study [49,50] showed that the CO 2 concentration at night after 12.00 a.m. exceeded 2300 ppm (room occupied by 2 people was not ventilated, microventilation was not used at the windows, the house was insulated with an ETICS and no other measures were taken, such as central system ventilation, air conditioning, etc.) [52].…”
Section: Characteristics Of External Walls Of Prefab Buildings In Con...mentioning
confidence: 87%
See 4 more Smart Citations
“…Measurements in this study [49,50] showed that the CO 2 concentration at night after 12.00 a.m. exceeded 2300 ppm (room occupied by 2 people was not ventilated, microventilation was not used at the windows, the house was insulated with an ETICS and no other measures were taken, such as central system ventilation, air conditioning, etc.) [52].…”
Section: Characteristics Of External Walls Of Prefab Buildings In Con...mentioning
confidence: 87%
“…grid and damage to the lamellas; (b) insufficient anchoring of insulating mineral wool; (c) example of post-thermally insulated external wall; (d) example of an additionally thermally insulated building only up to the 6th aboveground floor due to the quality of the material, the use of which at higher floors would not comply with fire safety regulations (Photo source: Author's archive [29,30]).…”
Section: Energy Heat and Renovation Of Prefabricated Housing Developm...mentioning
confidence: 99%
See 3 more Smart Citations